REFORMULASI KEWENANGAN MPR PASCA AMANDEMEN UUD NRI 1945 - Haryadi, Dwi (PROGRESIF: Jurnal Hukum, 2018)
People’s consultative assembly (MPR) from the beginning is formed as an institution with consensus principle, a principle of people’s consultative through consultative agency. The position and the authority of consultative agency started to change significantly after the amandements of 1945’s constitution. Even some opined that people’s consultative assembly is no longer required. There are several important issues that will be discuss as the main topic in this paper. First, development planning vs broad outlines of the nations direction (GBHN). Second, the authority of people’s consultative assembly to set the regulating provisions. Third, the authority of people’s consultative assembly to provide a constitutional interpretation. Fourth, this assembly reviewed it’s own provisions. Fifth, this assembly issued a decree inaugurating of president and vice president. These fifth reformulation issues are crucial among the dynamics of our state administration system and our current conditions, also in order to strengthen the functions of the people’s consultative assembly as a center for people's representation.